Pendampingan Instrumen Penilaian Mata Pelajaran Pekerjaan Dasar Teknik Mesin Berbasis SKNNI di SMK - Sahala Siallagan; Janter P Simanjuntak; Ika Nazira; Lia Maharani (Jurnal Masyarakat Indonesia (Jumas), 2024)
Community Service (PKM) aims to improve the competence of teachers in designing and implementing assessment instruments for basic mechanical engineering subjects based on SKNNI in vocational high schools. The Indonesian National Work Competence (SKKNI) is a formulation of work abilities that include aspects of knowledge, skills and/or expertise and work attitudes that are relevant to the implementation of tasks and job requirements as stipulated in accordance with the provisions of laws and regulations. This standard is used by vocational education units as a reference for the standard of competency for their students' expertise. Student competencies and expertise need to be known through assessment. The assessment aims to determine the extent of student learning outcomes or information about the achievement of student competencies. This activity is carried out with several stage methods, namely: (1) analysis of community situations (2) identification of problems (3) determining work objectives (4) problem-solving plans (5) social approaches (6) implementation of activities (7) evaluation of activities and results. The results of show, namely 1) Training participants know about the basic concepts of SKNNI-based instruments (Independent curriculum). 2) Training participants can create and design assessment instruments that suit the needs of students. 3) Training participants can apply student assessment instruments. Therefore, this activity is expected to help teachers become competent and professional teachers in teaching and also competent and professional in designing and implementing SKNNI-based assessment instruments in Mechanical Engineering subjects that suit the learning needs in vocational high schools.